ANALISIS EFISIENSI ANGGARAN PENDIDIKAN DALAM PERSPEKTIF ISLAM: Analysis of Education Budget Efficiency in an Islamic Perspective - Firman Robiansyah; Annisa Nur Fadillah; Nuril Khairiyah; Siti Nurkholizah; Gavin Sangraha Rahmat (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study analyzes the efficiency of the education budget from an Islamic perspective by highlighting the principles of transparency, accountability, and resource optimization. In Islam, the efficiency of the education budget aims to avoid waste and ensure fair and sharia-compliant financial distribution. This study uses a literature study method by analyzing various relevant literature. The results of the study indicate that the principle of efficiency in Islam can be applied through funding sources such as zakat, waqf, and alms that are managed professionally. In addition, community participation in financing education can increase the effectiveness of budget use. However, the budget efficiency policy also faces challenges, especially in the context of government policies, such as cutting the education budget which risks reducing the welfare of educators and the quality of education. Therefore, the implementation of efficiency must consider the balance between savings and meeting the needs of quality education, by involving strict supervision and public participation to remain in line with the principles of justice in Islam. Penelitian ini menganalisis efisiensi anggaran pendidikan perspektif Islam dengan menyoroti prinsip transparansi, akuntabilitas, dan optimalisasi sumber daya. Dalam Islam, efisiensi anggaran pendidikan bertujuan menghindari pemborosan serta memastikan distribusi keuangan yang adil dan sesuai syariah. Studi ini menggunakan metode studi kepustakaan dengan menganalisis berbagai literatur yang relevan. Hasil penelitian menunjukkan bahwa prinsip efisiensi dalam Islam dapat diterapkan melalui sumber pendanaan seperti zakat, wakaf, dan sedekah yang dikelola secara profesional. Partisipasi masyarakat dalam pembiayaan pendidikan juga dapat meningkatkan efektivitas penggunaan anggaran. Namun, kebijakan efisiensi anggaran menghadapi tantangan, terutama dalam konteks kebijakan pemerintah, seperti pemangkasan anggaran pendidikan yang berisiko mengurangi kesejahteraan tenaga pendidik dan kualitas pendidikan. Oleh karena itu, implementasi efisiensi anggaran harus mempertimbangkan keseimbangan antara penghematan dan pemenuhan kebutuhan pendidikan berkualitas, dengan melibatkan pengawasan ketat dan partisipasi publik agar selaras dengan prinsip keadilan dalam Islam. Kata Kunci : Anggaran Pendidikan; Efisiensi Anggaran; Kebijakan Pemerintah; Kualitas Pendidikan; Perspektif Islam.